Surgical management of congenital sternal cleft in a pediatric patient with PHACES syndrome - Landeros Muñoz, Manuel; Lara, Luis Francisco Sanchez; Pérez, Fermín Cazares; Yarza, Miguel Jimenez (International Journal of Research in Medical Sciences, 2025)
PHACES syndrome, first described in 1978 and named in 1996, is a rare disorder involving multiple malformations, including abnormalities of the posterior fossa, cervicofacial segmental hemangiomas, cerebrovascular arterial anomalies, cardiac or large vessel defects, ocular abnormalities and sternal defects such as the sternal cleft. It predominantly affects females, with a ratio of 9:1 and is seen in 2–3% of infantile hemangioma cases. Some patients may also present with thyroid disorders. The sternal cleft, one of the anomalies associated with PHACES syndrome, is a rare congenital malformation caused by a failure in the fusion of the sternal midline during embryonic development. It can be classified as partial or complete, with the superior partial cleft being the most common form. This defect compromises the protection of mediastinal organs and can result in varying degrees of respiratory distress. Diagnosis is typically straightforward through inspection and palpation at birth.